Atypical outcome of middle ear cholesteatoma: Case report - Coelho, Tamires Carvalho; Miranda, Álvaro Palhares Ferreira de; Bezerra, Ariel Patrick Alves; Oliveira, Breno Andrade de; Rafael, Caroline Ruben Fernandes; Araújo, Fabrina Filgueiras de; Oliveira, Gabrielle Freitas de; Lima, Lara Hellen Feitoza Sandes; Cavalcanti, Lara Miná de Britto; Silva, Leticia Maria Soares da; Lins, Luciana Brito da Silva; Nascimento, Magda Cristina Leonardo de Souza Costa; et al. (Seven Editora, 2024)
The present study aimed to describe a case of middle ear cholesteatoma with recurrence after surgical removal, followed by an atypical outcome. A 40-year-old male patient sought medical attention complaining of otalgia and ear fullness in the left ear. Magnetic resonance imaging showed fluid content and mastoid cells occupying the left tympanic cavity, with foci of diffusion restriction in the tympanic box and antrum measuring about 1.4 cm, which is compatible with left middle ear cholesteatoma. The patient was then submitted to two surgical procedures (an endoscopic tympanoplasty and a closed mastoidectomy), at an interval of four months, to completely remove the tumor. After 3 years and 6 months, the patient had recurrence of cholesteatoma. On the day before the surgery scheduled to remove the recurrent tumor, magnetic resonance imaging revealed the absence of cholesteatoma, suggesting a spontaneous cure. The cure or natural disappearance of the tumour opens new research perspectives for the medical sciences. DOI:https://doi.org/10.56238/sevened2024.001-045